The assessment of cholinesterase from gills of Anabus testudineus as detection of metal ion - Low, Weini (2015)
Cholinesterase from the gill of Anabus testudineus contains mostly AChE. It was partially purified by ammonium sulphate precipitation and DEAE cellulose using ion exchange chromatography with 4.890U of specific activity, 11.7 of purification fold and 3.0% yield. Optimum pH for AChE in gill of A. testudineus is 8 using Tris-HCl buffer at temperature 25°C. The optimum acetylthiocholine iodide concentration is 2.5 mM with Vmax 2.533 and Km 0.8802 in which the catalytic efficiency of 2.88. For metal ion inhibition, 10 metal ions were tested and AChE in gill of Anabus testudineus showed a critically low enzyme activity towards mercury in which the activity is inhibited by 99.05%. However, cobalt and silver had no inhibitory effect on AChE. From IC50, only 0.0123 ppm of Hg was required to reduce the enzyme activity by half.